The effect of eye disease, cataract surgery and hearing aid use on multisensory integration in ageing. (December 2020) - Hirst, Rebecca J.; Setti, Annalisa; De Looze, Céline; Akuffo, Kwadwo O.; Peto, Tunde; Kenny, Rose A.; Newell, Fiona N.
Abstract: Sensory impairment is common in ageing, as are approaches to treat it. However, the impact of age-related sensory impairment upon multisensory perception remains unexplored, despite the multisensory nature of our environment. Here, we used data from The Irish Longitudinal Study of Ageing (TILDA) to investigate whether common, age-related eye diseases (cataracts, glaucoma and Age-Related Macular Degeneration, ARMD) and clinical intervention to improve sensory function (cataract removal and hearing aids) influence multisensory integration in older adults. Integration was measured using the Sound-Induced Flash Illusion (SIFI), and the extent to which identifying two flashes was improved by accompanying auditory information ("visual gain"). Visual gain was not influenced by eye disease or treatment. For the SIFI, participants self-reporting cataracts, ARMD or glaucoma were as susceptible as healthy controls, even when controlling for age, sex, cognition, self-reported vision/hearing and visual acuity. In a second analysis using retinal photographs, glaucoma and ARMD (hard drusen) did not influence susceptibility relative to controls. However, participants with soft drusen ARMD were more susceptible to the illusion at long Stimulus-Onset Asynchronies (SOAs) compared with controls. Following this, we identified groups reporting bilateral cataract removal or hearing aid acquisition >4 years and <2 years prior to assessment, enabling comparison of longer- and shorter-term effects of interventions. Cataract removal groups did not differ from controls. Longer-term hearing aid users were less susceptible to the SIFI at short SOAs compared with controls. Our findings suggest that multisensory integration in ageing might be specifically influenced by ARMD (soft drusen) and hearing aid use.